ANALISIS NILAI-NILAI PENDINDIKAN ISLAM DALAM NOVEL NEGERI 5 MENARA KARYA A. FUADI - Arnanda, Rizky Yuda (Universitas Dharmawangsa, 2024)
This study aims to determine (1) the value of Akidah education contained in the novel Negeri 5 Menara by A. Fuadi, (2) the value of worship education contained in the novel Negeri 5 Menara by A. Fuadi, (3) the value of Akhlak education contained in the novel Negeri 5 Menara by A. Fuadi. The research method is qualitative library research, a set of activities related to library data collection methods, reading and recording and processing of research materials. The object of research in this paper is the novel Negeri 5 Menara by A. Fuadi. The stages that must be taken in this library research are collecting research materials, reading library materials, making research notes, and processing research notes. The data analysis technique uses the documentation method, which is to search and collect data by searching and reviewing primary and secondary data sources. The results of this study are presented (1) There is the value of Islamic education, namely Akidah education in the form of God, (2) There is the value of Gairuh Mahdah worship education in the form of studying, reading the Qur'an, (3) There is the value of Akhlak education in the form of Amar ma'ruf nahi munkar, sincerity, honesty, effort, gratitude, patience, forgiveness, and Tawakal.